1995
DOI: 10.1080/00207149508409376
|View full text |Cite
|
Sign up to set email alerts
|

Modifying Hypnotizability: A New Component Analysis

Abstract: The effects of the Carleton Skills Training Program (CSTP) on hypnotizability were compared to those of a modified training program in which instructions for physical enactment of the response were omitted. After training, subjects in the original CSTP reported an increase in the extent to which they intentionally enacted suggested behaviors. In contrast, subjects in the modified training program reported increased fantasy without voluntary physical enactment. Nevertheless, both training programs increased beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…Measures of hypnotic response expectancy usually focus on predicting behavioral responses (e.g., Council, Kirsch, Vickery, & Carlson, 1983). In the more recent studies, measures of expected subjective experiences were added (Gearan et al, 1995;. Consistent with our hypothesis, these two measures were very highly correlated.…”
Section: Response Sets and Environmentally Triggered Behaviorsupporting
confidence: 66%
See 2 more Smart Citations
“…Measures of hypnotic response expectancy usually focus on predicting behavioral responses (e.g., Council, Kirsch, Vickery, & Carlson, 1983). In the more recent studies, measures of expected subjective experiences were added (Gearan et al, 1995;. Consistent with our hypothesis, these two measures were very highly correlated.…”
Section: Response Sets and Environmentally Triggered Behaviorsupporting
confidence: 66%
“…More specific to the issue of involuntariness, Lynn, Nash, Rhue, Frauman, and Sweeney (1984) reported that voluntary control over hypnotic responses-as gaged by the ability of highly responsive participants to resist suggestions-can be influenced strongly by expectancy-altering information. Similarly, measured expectancies are highly correlated with behavioral and subjective response to suggestion, and expectancy manipulations can increase responsiveness greatly (Gearan, Schoenberger, & Kirsch, 1995;Wickless & Kirsch, 1989). These data suggest that the subjective experience of hypnosis, including the experience of involuntariness, may be shaped by expectancy (see Lynn et al, 1990;Spanos, 1986b).…”
Section: The Construction Of Subjective Experiencementioning
confidence: 90%
See 1 more Smart Citation
“…Subsequent studies using refined expectancy measures have confirmed this strong association between expectancy and responses to suggestion (Council, Kirsch, & Hafner, 1986;Gearan, Schoenberger, & Kirsch, 1995;Johnston, Chajkowaski, DuBreuil, & Spanos, 1989;Kirsch, Silva, Comey, & Reed, 1995;Vickery & Kirsch, 1991). Kirsch et al (1995) presented three data sets in which hypnotic suggestibility was correlated with absorption, fantasy proneness, dissociation, attitudes toward hypnosis, and response expectancies.…”
Section: Specific Ratingsmentioning
confidence: 91%
“…Expectancy Questionnaire (Gearan, Schoenberger, & Kirsch, 1995). The Expectancy Questionnaire assesses participants' anticipated reaction to each of the suggestions they will be given across three different dimensions.…”
Section: Pre-induction Measuresmentioning
confidence: 99%